Electroformation of coatings modified with silver on magnesium alloys for biomedical applications - Loperena, Ana Paula (2020)
Three different films modified with silver species were considered to enhance the corrosion resistance of AZ91D Mg alloy and to impart its surface with antibacterial activity. First, coatings were electrodeposited under potentiostatic conditions in electrolyte solutions containing Na2MoO4 and/or Ce(NO3)3 as main compounds, and H2O2, ascorbic acid or citric acid as additives. Incorporation of silver species was done by immersion of the samples in AgNO3 solutions. The obtained modified films were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The corrosion protection properties of the films were examined in a simulated physiological solution by open circuit measurements, linear polarization and electrochemical impedance spectroscopy (EIS). The antibacterial effect of the coatings was evaluated using Escherichia coli bacteria. Cerium and molybdenum-based coating modified with silver provides superior antibacterial and anticorrosive properties compared to the other films studied.